A retrospective cohort study: risk factors for hip abductor disruption in patients undergoing total hip arthroplasty and hemiarthroplasty - Tiwana, Hardeep S.; Dolgov, Vadim S.; Schmidt, Carsten; Pham, Quyen P.; Schmitz, Miguel (International Journal of Research in Orthopaedics, 2026)
Background: Hip abductor pathology is increasingly recognized as a contributor to impaired mobility and suboptimal outcomes following total hip arthroplasty (THA) and hemiarthroplasty. However, the prevalence and clinical significance of abductor disruption across fracture-related and elective indications remain unknown. Methods: We conducted a retrospective cohort study of 67 patients who underwent total hip arthroplasty, hemiarthroplasty, or hip abductor repair between 2017 and 2023, identified using CPT codes from the AthenaOne healthcare system and Alpine Ortho Spine Clinic database. Results: Fracture patients were significantly older than elective total hip arthroplasty patients (76.8±8.2 versus 66.4±7.9 years, p<0.001) and demonstrated a higher proportion of Dorr type C femora (p=0.02). Both iliopsoas and quadriceps strength improved postoperatively across the cohort (iliopsoas: 2.7±0.9 to 3.4±0.8, p<0.01; quadriceps: 3.0±0.8 to 3.6±0.7, p<0.01). Elective patients showed greater strength gains than fracture patients (iliopsoas Δ0.9 versus Δ0.5, p=0.03; quadriceps Δ0.8 versus Δ0.4, p=0.04). Trendelenburg gait was more prevalent preoperatively in fracture patients (38% versus 19%, p=0.04) and remained higher at follow-up (24% versus 12%, p=0.05). Conclusions: Pre-existing hip abductor disruption is common in both fracture and elective arthroplasty populations. These findings highlight the importance of recognizing abductor pathology as a modifiable factor influencing recovery and support the role of targeted perioperative management and rehabilitation strategies.